Study on establishment of the on-street parking in Urban Residential Area - Taking Harbin as an Example. Issue 1 (May 2021) - Xiqiao, Zhang; Xu, Sun; Xiaoyan, Zhu
Abstract: In order to alleviate the problem of "parking is difficult and disorderly" in urban residential areas, the setting of on-road parking in Harbin residential areas is studied and explored. First of all, this paper uses the method of combining manual field survey and inquiry survey to investigate the on road parking settings in residential areas, and summarizes the problems such as the imbalance between supply and demand of parking in the outlet, the unreasonable settings, and the imperfect prompt signs. Based on this, this paper puts forward the corresponding countermeasures on three aspects of parking space settings, parking time settings, and parking space settings, in order to provide ideas and countermeasures for other urban residential parking settings.